THE IMPACT OF ACCOUNTING INFORMATION SYSTEMS EFFECTIVENESS ON FINANCIAL REPORTING QUALITY: AN ANALYTICAL STUDY OF THE IRAQ STOCK EXCHANGE (2011-2023) - Haifa Kazem Ibrahim (Scholars Digest Publishing, 2026)
This research aims to evaluate the relationship between the effectiveness of the accounting information system and the quality of financial reports of companies listed on the Iraq Stock Exchange. The importance of this study stems from the vital role that accounting information systems play in providing accurate and reliable information that supports sound economic decision-making, especially in light of economic developments and crises that increase the need of stakeholders and investors for high-quality information. The study assumes a statistically significant relationship between the quality of accounting information and the quality of financial reports, as well as between the quality of financial reports and both the market value of companies and the liquidity of their shares. To achieve its objectives, the study reviewed previous literature and analyzed the factors influencing the quality of financial reports, while identifying indicators for measuring the effectiveness of accounting information systems. The research relied on analyzing the financial data of companies listed on the Iraq Stock Exchange during the period from 2011 to 2023. Multiple statistical methods were used to analyze the relationship between the study variables, such as correlation and multiple regression analyses. The results revealed a strong positive correlation between the independent variables (quality of accounting information) and the dependent variable (quality of financial reports). It was found that 69% of the variations in the quality of financial reports are attributable to changes in the quality of accounting information. The findings also demonstrated a significant impact of the market index on the quality of financial reports, showing that 72% of the variations in report quality are affected by the Iraq Stock Exchange index. Based on these results, the study recommends strengthening supervision to ensure compliance with international accounting standards, developing regulations and systems that enhance the quality of accounting information, investing in modern accounting information systems, and promoting a culture of transparency and accountability within companies.
Keywords: Accounting Information Systems, Quality of Financial Reports, Accounting Information, Qualitative Characteristics of Information, Iraq Stock Exchange.